The Rebellion in the Cevennes, an Historical Novel. Vol. II. - Tieck, Ludwig, 1773-1853; Burette, Madame (Salt Lake City, UT : Project Gutenberg, 2010)
"The Rebellion in the Cevennes, an Historical Novel. Vol. II." by Ludwig Tieck is a historical novel written in the mid-19th century. The narrative centers around a tumultuous time in the Cevennes region of France, focusing on characters such as Edmond and Cavalier as they navigate a backdrop of personal struggles and communal conflicts related to rebellion and faith. Themes of loyalty, personal redemption, and the quest for freedom shape the story's unfolding drama. The opening of the novel introduces us to Edmond, who, recovering from an injury, feels compelled to return to his home, only to find it threatened by intruders. Instinctively taking action, he warns his comrades and confronts the danger posed by robbers, signifying his brave character. As he grapples with the chaos around him and his emotional ties to family, the chapter reveals friendships and alliances amidst the struggles of rebellion. Cavalier and other characters like Roland and the mysterious Lacoste begin to intertwine within this personal and political upheaval, hinting at the larger narrative that explores themes of vengeance, mercy, and the complexities of human nature against the backdrop of war. (This is an automatically generated summary.)
Release date is 2010-03-22
Produced by Charles Bowen, from page scans by Google Books.
Keywords: Historical fiction; German fiction -- Translations into English; France -- History -- Insurrection of the Camisards, 1702-1710 -- Fiction